The supervised internship as space for reflection on teaching practices in the initial training of chemistry teachers at Federal Institute of Rio de Janeiro (IFRJ) – Nilópolis (Research, Society and Development, 2020)
Teacher training, specifically, the supervised internship, has been the subject of discussion among several researchers in the fields of teaching and education in Brazil for a long time. In order to understand the perception that graduates of the Chemistry Degree course at IFRJ, Nilópolis campus, have on the contribution and importance of the Supervised Internship in their teacher training, in several aspects, this work was carried out. This research is a qualitative investigation carried out with students who attended at least one of the three mandatory supervised internships offered in the course. The data collection instrument used was an open questionnaire, consisting of five open questions, and the methodology used in the research was Content Analysis, according to Bardin, which predicts the categorization of the content of the answers obtained by the frequency of the appearance of terms equal to or terms with the same semantic content. Through the analysis of the research results it was possible to conclude that the future teachers understand the supervised internship, in most cases, as the practical part of their training course. The supervised internship should be understood by future teachers as a space that allows the construction of the teaching identity and moments of reflection on the teaching practice.